IDENTIFIKASI KESULITAN BELAJAR FISIKA PADA SISWA RSBI : STUDI KASUS DI RSMABI SE KOTA SEMARANG (UPEJ Unnes Physics Education Journal, 2012)
This study aims to map the physical learning difficulties and the factors that caused the student RSMABI se Semarang. The research use qualitative methods were implemented in SMAN 2 Semarang and Semarang SMAN 4. Data on students physics learning difficulties derived from a description of student test results sheet. Data factors that cause learning difficulties derived from physics student sheet questionnaire completed by the students. Learning difficulty level data obtained from the analysis of the percentage of descriptive analytical test results of students were consulted with learning difficulty level classification table. Data learning difficulties factors derived from the descriptive analysis of the percentage of the completed questionnaires were consulted with learning difficulties factor classification table. Results showed difficulties in learning physics concepts mastery indicators. The factors that cause learning difficulties physics include interest, aptitude, motivation, intelligence, school facilities, teachers, facilities or infrastructure and support, and activities have the same level that is sufficient cause learning difficulties in students RSMABI physics se Semarang.